Nosocomial RSV-related In-hospital Mortality in Children <5 Years: A Global Case Series. Issue 1 (8th November 2022) - Löwensteyn, Yvette N.; Willemsen, Joukje E.; Mazur, Natalie I.; Scheltema, Nienke M.; van Haastregt, Nynke C. J.; Buuren, Amber A. A. ten; van Roessel, Ichelle; Scheepmaker, Dunja; Nair, Harish; van de Ven, Peter M.; Bont, Louis J.; ,
Abstract : Background: According to the World Health Organization, the global burden of nosocomial infections is poorly characterized as surveillance systems are lacking. Nosocomial infections occur at higher rates in low- and lower-middle-income countries (LMICs) than in high-income countries (HICs). Current global RSV burden estimates are largely based on community-acquired infection. We aimed to characterize children with nosocomial RSV-related mortality and to understand the potential impact of RSV immunization strategies. Materials: RSV GOLD is a global registry of children younger than 5 years who died with laboratory-confirmed RSV infection. We compared clinical and demographic characteristics of children with nosocomial and community-acquired RSV in-hospital mortality. Results: We included 231 nosocomial and 931 community-acquired RSV-related in-hospital from deaths from 65 countries. Age at death was similar for both groups (5.4 vs. 6 months). A higher proportion of nosocomial deaths had comorbidities (87% vs. 57%; P < 0.001) or was born preterm (46% vs. 24%; P < 0.001) than community-acquired deaths. The proportion of nosocomial deaths among all RSV deaths was lower in LMICs than in upper-middle-income countries (UMICs) and HICs (12% vs. 18% and 26%, respectively). Conclusions: This is the first global case series of children dying with nosocomial RSV infection. Future infant-targeted immunization strategies could prevent the majority of nosocomial RSV-related deaths. Although nosocomial RSV deaths are expected to occur at highest rates in LMICs, the number of reported nosocomial RSV deaths was low in these countries. Hospital-based surveillance is needed to capture the full burden of nosocomial RSV mortality in LMICs.